ID22 – the high-resolution powder-diffraction beamline at ESRF - Andrew Fitch; Catherine Dejoie; Ezio Covacci; Giorgia Confalonieri; Ola Grendal; Laurent Claustre; Perceval Guillou; Jérôme Kieffer; Wout de Nolf; Sébastien Petitdemange; Marie Ruat; Yves Watier (Journal of Synchrotron Radiation, 2023)
Following Phase 2 of the upgrade of the ESRF in which the storage ring was replaced by a new low-emittance ring along with many other facility upgrades, the status of ID22, the high-resolution powder-diffraction beamline, is described. The beamline has an in-vacuum undulator as source providing X-rays in the range 6–75 keV. ID22's principle characteristics include very high angular resolution as a result of the highly collimated and monochromatic beam, coupled with a 13-channel Si 111 multi-analyser stage between the sample and a Dectris Eiger2 X 2M-W CdTe pixel detector. The detector's axial resolution allows recorded 2θ values to be automatically corrected for the effects of axial divergence, resulting in narrower and more-symmetric peaks compared with the previous fixed-axial-slit arrangement. The axial acceptance can also be increased with increasing diffraction angle, thus simultaneously improving the statistical quality of high-angle data. A complementary Perkin Elmer XRD1611 medical-imaging detector is available for faster, lower-resolution data, often used at photon energies of 60–70 keV for pair-distribution function analysis, although this is also possible in high-resolution mode by scanning up to 120° 2θ at 35 keV. There are various sample environments, allowing sample temperatures from 4 K to 1600°C, a capillary cell for non-corrosive gas atmospheres in the range 0–100 bar, and a sample-changing robot that can accommodate 75 capillary samples compatible with the temperature range 80 K to 950°C.